2017
DOI: 10.1016/j.midw.2017.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal weight management: Diet, physical activity, and gestational weight gain in early pregnancy

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…Despite recognised public health guidelines encouraging PA during pregnancy, PA levels often decline during pregnancy, particularly during the second and third trimesters, and remain low until at least three months after birth [3], or completely cease [4]. A possible reason for this decline is that women are more likely to change the type of PA they engage in (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite recognised public health guidelines encouraging PA during pregnancy, PA levels often decline during pregnancy, particularly during the second and third trimesters, and remain low until at least three months after birth [3], or completely cease [4]. A possible reason for this decline is that women are more likely to change the type of PA they engage in (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…switching to lower intensity activities which may not provide as many health benefits [3]). Women may also cease their PA as a result of their lived experiences of being pregnant and/or their perceptions of possible risk to the fetus [4].…”
Section: Introductionmentioning
confidence: 99%
“…Comparable with findings of an earlier study by Groth and Kearney (2009), women wanted more information on pregnancy weight management but were often offered advice inconsistent with national guidelines. In contrast, Swift et al (2017) found that women in the UK changed their dietary intake and activity behaviour in response to physical cues rather than advice from health professionals.…”
Section: How Do Included Papers Contribute To the Evidence?mentioning
confidence: 88%
“…pregnancy and parenthood) that present 'teachable moments' (84) . Encouraging health promoting behaviour change is far from simple and there has been much interest recently in how clinicians and others in relevant positions go about offering lifestyle advice and whether there may be certain points in life (e.g.…”
Section: Lifestyle Habits and Choicesmentioning
confidence: 99%
“…Encouraging health promoting behaviour change is far from simple and there has been much interest recently in how clinicians and others in relevant positions go about offering lifestyle advice and whether there may be certain points in life (e.g. pregnancy and parenthood) that present 'teachable moments' (84) . Unless delivered in an appropriate way, a person's motivation to change often declines.…”
Section: Lifestyle Habits and Choicesmentioning
confidence: 99%